Impact of left ventricular outflow tract calcium on valve geometry in self‐expanding transcatheter aortic‐valve replacement. Issue 3 (20th June 2022) - Medranda, Giorgio A.; Rogers, Toby; Fuery, Michael; Case, Brian C.; Collins, Erin C.; Ali, Syed W.; Zhang, Cheng; Wang, John C.; Weissman, Gaby; Cohen, Jeffrey E.; Shults, Christian C.; Satler, Lowell F.; et al.
Abstract: Objectives: Evaluate transcatheter heart valve (THV) geometry according to left ventricular outflow tract (LVOT) calcium degree and its impact on hemodynamics and outcomes in patients undergoing transcatheter aortic valve replacement (TAVR) with a contemporary self‐expanding THV. Background: LVOT calcium remains challenging for contemporary THVs. LVOT calcium location and degree may affect THV deployment and impact flow patterns and shear stress, accelerating THV degeneration. Methods: EPROMPT (CoreValve Evolut Pro Prospective Registry; NCT03423459) is a prospective, investigator‐initiated, multicenter registry of patients undergoing TAVR using CoreValve Evolut PRO/PRO + THVs. A total of 107 patients were enrolled in EPROMPT's computed tomography (CT) cohort between January 2018 and October 2021. These patients underwent follow‐up CT scan 30 days post‐TAVR. We analyzed THV geometry and its interaction with the aortic root following deployment using 30‐day post‐TAVR CT in patients with none/mild versus moderate/severe LVOT calcium. Results: Thirty‐day THV inflows were less eccentric in the short axis in patients with none/mild versus moderate/severe LVOT calcium (1.16 ± 0.09 vs. 1.21 ± 0.12; p  = 0.007). THV became more circular and was similar between both cohorts at the THV waist (1.08 ± 0.06 vs. 1.09 ± 0.11; p  = 0.551), leaflet tips (1.03 ± 0.04 vs. 1.05 ± 0.09; p  = 0.299), and THV outflow (1.04 ± 2.2 vs. 1.03 ± 2.7; p  = 0.143). Thirty‐day > mild paravalvular leak was low in both cohorts (1.5% vs. 2.4%; p  = 0.724); mean gradients were similar (7.7 ± 3.6 vs. 7.7 ± 3.4 mmHg; p  = 0.955). Conclusions: Despite inflow deformities observed in patients with moderate/severe LVOT calcium, Evolut PRO/PRO + conforms to elliptical aortic annuli, maintaining circularity and proper function at the leaflets and outflow, even in patients with moderate/severe LVOT calcium.